[Rezension von: Němec, Damián, 1960-, Annotated legal documents on Islam in Europe : Czech Republic] - Přibyl, Stanislav (Ecumeny and law, 2022)
Recenzja wspomnianej książki stworzona przez doc. Stanislav Přibyl.